Free Model of Sentence Classifier for Automatic Extraction of Topic Sentences - M.L. Khodra; D.H. Widyantoro; E.A. Aziz; B.R. Trilaksono (Journal of ICT Research and Applications, 2011)
This  research  employs  free  model  that  uses  only  sentential  features without paragraph context  to extract topic sentences of a paragraph. For finding optimal  combination  of  features,  corpus-based  classification  is  used  for constructing a sentence classifier  as the model.  The sentence classifier is trained by  using Support Vector Machine  (SVM).  The experiment shows that position and meta-discourse features are more important  than syntactic features  to extract topic  sentence,  and  the  best  performer  (80.68%)  is  SVM  classifier  with  all features.